High-Grade Endometrial Mesenchymal Sarcoma: Current Status and Future Trends - Zhang, Lushuang; Zhao, Liubiqi (Clinical Journal of Obstetrics and Gynecology, 2023)
Endometrial Stromal Sarcoma (ESS) is a rare gynecological malignancy originating from endometrial stromal tissue. Representing only a tenth of uterine malignant tumors, ESS is categorized into Low-Grade (LGESS) and High-Grade (HGESS) based on nuclear division. Interestingly, prognostic studies have found no strong correlation between ESS prognosis and nuclear division activity. Undifferentiated Uterine Sarcoma (UUS) represents a spectrum of tumors with varied morphological, clinical, and prognostic features, and lacks a standardized naming convention. In 2014, the World Health Organization grouped ESS into LGESS, HGESS, and UUS based on clinical and pathological attributes. HGESS, despite its rarity, is notorious for its poor prognosis and low survival rate. Its early detection is complicated due to its asymptomatic presentation and ambiguous pathogenesis, leading to debates over treatment approaches. This article delves into the recent research developments concerning HGESS.